Conditions of Stable Ignition of Coal-Water Slurry Containing Petrochemicals Based on Carbon Residue of Tire Pyrolysis; Chemical and Petroleum Engineering; Vol. 53, iss. 1-2 - Vershinina K. Yu. Kseniya Yurievna; Glushkov D. O. Dmitry Olegovich; Strizhak P. A. Pavel Alexandrovich; Shabardin D. P. Dmitry Pavlovich (2017, 2017)
Title screen